World of Warcraft Programming: A Guide and Reference for Creating WoW Addons - Whitehead, J; Roe, R (John Wiley and Sons, 2010)
World of Warcraft has entered a new dimension. Take command of it by modifying the interface with your own unique addons. Whether your goal is to enhance addons you already use, to enlarge your arsenal by creating some all-new features, or to immerse yourself in the programming as well as the game, this book will be your oracle. Learn the arcane languages of Lua and XML and master the craft of addon creation!